Organ-Specific Effects of Low Dose Radiation Exposure: A Comprehensive Review - Shin, Eunguk; Lee, Sungmin; Kang, Hyunkoo; Kim, Jeongha; Kim, Kyeongmin; Youn, HyeSook; Jin, Young Woo; Seo, Songwon; Youn, BuHyun (Frontiers in Genetics, 2020)
Ionizing radiation (IR) is a high-energy radiation whose biological effects depend on the irradiation doses. Low-dose radiation (LDR) is delivered during medical diagnoses or by an exposure to radioactive elements and has been linked to the occurrence of chronic diseases such as leukemia and cardiovascular diseases. Though epidemiological research is indispensable for predicting and dealing with LDR-induced abnormalities in individuals exposed to LDR, little is known about epidemiological markers of LDR exposure. Moreover, difference in the LDR-induced molecular events in each organ has been an obstacle to a thorough investigation of the LDR effects and a validation of the experimental results in in vivo models. In this review, we summarized the recent reports on LDR-induced risk of organ-specifically arranged the alterations for a comprehensive understanding of the biological effects of LDR. We suggested that LDR basically caused the accumulation of DNA damages, controlled systemic immune systems, induced oxidative damages on peripheral organs, and even benefited the viability in some organs. Furthermore, we concluded that understanding of organ-specific responses and the biological markers involved in the responses is needed to investigate the precise biological effects of LDR.